Peran Kecerdasan Emosional Dan Kecerdasan Spiritual Sebagai Prediktor Empati Sosial Siswa Di SMK Muhammadiyah Berau - Ziaul Rahman Baehaqi; Darul Ihsan; Ibnu Abbas; Muhammad Alfi Syahrin (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study aims to analyze the role of emotional intelligence and spiritual intelligence as predictors of students’ social empathy at SMK Muhammadiyah Berau. This research employed a quantitative approach with a correlational method. The sample consisted of 50 students selected using proportional random sampling. Data were collected through Likert-scale questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis. The results showed that emotional intelligence and spiritual intelligence simultaneously had a significant effect on social empathy (Sig. = 0.000 < 0.05) with a coefficient of determination (R²) of 0.808, indicating that 80.8% of the variance in social empathy is explained by both variables. Partially, emotional intelligence had a positive and significant effect on social empathy (Sig. = 0.009), while spiritual intelligence showed a more dominant influence (Sig. = 0.000; β = 0.615). These findings indicate that students’ social empathy is shaped not only by emotional regulation abilities but also by the internalization of spiritual values. Therefore, integrating emotional and spiritual intelligence development into the learning process is essential in strengthening character education in vocational schools.